INFLUENCE OF JAMU MADURA â€œEMPOT SUPERâ€ ON THE VAGINAL EPITHELIUM THICKNESS OF WHITE MICE (Rattus norvegicus) â€“ AN IN VIVO STUDY - Listiyana, Anik (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
The aim of this research is to determine the influence of jamu Madura â€œEmpot Superâ€ (JMES) on the vaginal epithelium thickness of Rattus norvegicus in vivo. This research is kind of â€œtrue experimental-post test only control group designâ€. The rats were given drinking JMES once daily PS (Per-Sonde) for a month, then the vagina was taken to be sample for HE colouring. The sample was observed by the binocular microscope (100 times magnification) to identify the changes in the thickness of their vaginal epithelium. Calculation of the vaginal epithelium thickness was counted on the 10 field of view chosen randomly by the blind method. The result show that the vaginal epithelium thickness increased with dose 0,17mg/BW, 0,34mg/BW, and 0,68mg/BW of JMES compared with negative control group. But, the vaginal epithelium thickness decrease at the dose 0,51mg/BW compared with negative control group.Â Keywords: Jamu Madura â€œEmpot Superâ€ (JMES), vaginal epithelium thickness, white mice (Rattus norvegicus), In Vivo study